Pentingnya pendidikan karakter di era digital - sitta14, amalia (Maliki Interdisciplinary Journal, 2025)
Character education has a very important role in shaping the next generation of the nation who have noble morals and good behavior, especially in an increasingly complex era. This article aims to review the meaning, purpose, and benefits of implementing character education in schools. This study uses a qualitative approach with a literature study method to analyze various written sources related to the topic of character education. The results of the analysis show that character education plays a role in shaping students' personalities, preventing social problems of adolescents, creating a responsible generation, providing for community life, and supporting students' academic achievement. It is recommended that character education be included in the curriculum and taught through examples and habits, with collaboration between schools, families, and communities. The implementation of character education is very important to produce the next generation of the nation who are not only intellectually superior, but also have noble character and good morals.